Narrative means towards literacy understandings: exploring transformations within literacies and migrating identities. An analysis of narrative reflections towards the development of critical reflective thinking by mature students in a classroom of wider access - Hutchings, Catherine Mary (Department of Psychology, 2015)
Includes bibliographical references.